Species of Rhodesiella from Guangdong, South China (Diptera: Chloropidae) - Xu, Yanling; Yang, Ding (Zootaxa, 2005)
Rhodesiella guangdongensis sp. nov. is described from Guangdong, China. Its relationship with related species of Rhodesiella is discussed.